The Histopathological Association of Non-alcoholic Fatty Liver Disease With Coronary Artery Atherosclerosis Grade: New aspects of NAFLD and coronary artery atherosclerosis - Gholami, Behnaz; Khoshbaten‬, Manouchehr; Eftekhari, Hamidreza; Razi Soofiyani, Saiedeh; Ghojazadeh‬‬‬‬‬‬‬‬, Morteza; Zaare Nahandi, Maryam; Vahedi, Amir; Ostadi, Ali; Banag‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬‬ozar Mohammadi, Ahad; Kamali Sabeti, Artin; BanagozarMohammadi, Ali; SamadiRad, Bahram; et al. (International Journal of Medical Toxicology and Forensic Medicine, 2024)
Background: The association between the severity of coronary atherosclerosis and histopathologic findings in patients with non-alcoholic fatty liver disease (NAFLD) is not entirely understood. Considering the gold standard method, this study evaluates the histopathologic association between the severity of NAFLD and the grades of coronary atherosclerosis. Methods: In this descriptive-analytical study, data from 205 cadavers who were referred to an Iranian (Tabriz) forensic medicine organization between 2015 and 2017 and underwent simultaneous liver and coronary artery biopsies were examined. Finally, 168 cases were entered based on the inclusion criteria. First, pathological slides of these cadavers were extracted from the forensic medicine archive and re-examined. Then, the selected cases’ blocks were extracted from the tissue block bank, and again, after preparing a new slide, they were stained with trichrome for accurate estimation of liver fibrosis. Results: The assessment of NAFLD histological status in the studied cases revealed that 75.6% of the cases were classified as severity I, 18.4% as severity II, and 6% as severity III. Most cases with coronary atherosclerosis were classified as American Heart Association staging (AHA), type V (19.6%), and normal (19.6%). There was no statistically significant relationship between the severity of simple steatosis, steatohepatitis, and NAFLD, with coronary atherosclerosis. In subjects with higher severity of coronary atherosclerosis, the liver fibrosis rate is also higher, but no statistically significant difference was observed. Conclusion: The present study revealed no significant histopathological association between NAFLD and coronary artery atherosclerosis grade.